2011
DOI: 10.3807/josk.2011.15.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Precise Test Sieves Calibration Method Based on Off-axis Digital Holography

Abstract: We describe, throughout a Mach-Zehnder interferometric configuration, a new test sieves calibration method based on off-axis digital holography. The experiment is conducted on a test sieve of square openings. The nominal sieve opening is 1.00 mm with maximum individual opening of 1.14 mm in size. The recorded off-axis hologram is numerically processed using Fresnel transforms to obtain an object wave (amplitude and phase). From the reconstructed phase, the average size of the illuminated openings has been meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…With respect to the automatic calibration of sieves, only the approaches proposed by Abdelsalam et al [4], Belan et al [12] and Guo et al [2] were found in our literature review. Abdelsalam et al [4] developed an approach based on off-axis digital holography and fast Fourier transform (FFT), in which a light beam emitted against the grid of the sieve is acquired by a CCD camera and the resultant image processed using the FFT, in order to reconstruct and analyze the grid. Although the authors claim that the method is robust and precise, they do not mention the error rate of the proposed system, in comparison with conventional methods, nor the time spent analyzing the sieve.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…With respect to the automatic calibration of sieves, only the approaches proposed by Abdelsalam et al [4], Belan et al [12] and Guo et al [2] were found in our literature review. Abdelsalam et al [4] developed an approach based on off-axis digital holography and fast Fourier transform (FFT), in which a light beam emitted against the grid of the sieve is acquired by a CCD camera and the resultant image processed using the FFT, in order to reconstruct and analyze the grid. Although the authors claim that the method is robust and precise, they do not mention the error rate of the proposed system, in comparison with conventional methods, nor the time spent analyzing the sieve.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, the accuracy of the measurement process can be significantly affected when the instrument or device to be calibrated has no data communication interface. In this case, the probability of the occurrence of human error is greatly increased, due to the various readings and transcriptions of data required, which constitute a stressful task [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibration of surfaces with high accuracy is needed for many applications in industry. [1][2][3][4][5][6][7][8][9][10][11][12][13] In some applications such as calibration of gauge blocks 14 and references of the interferometers, 15 it is of practical importance to estimate the uncertainty budget of the measurement result to verify the conformance of the components. 16 Optical interferometers have been extensively used as noncontact instruments for accurate surface measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) holographic imaging systems [1][2][3][4][5][6][7][8][9][10] have been investigated for achieving reliable and non-invasive recognition and for identifying biological micro /nano organisms [11][12][13][14]. The 3D holographic imaging system for biological microorganism analysis has a large number of biological applications such as medical diagnosis, medical therapeutics, bio-medical imaging, defense, and security.…”
Section: Introductionmentioning
confidence: 99%